Biopolitical Animation: A lockdown reading of Mandel's Station Eleven. (2nd January 2022) - Wolfe, Graham
Abstract : An obligatory entry on lists of 'essential pandemic reading', Emily St John Mandel's Station Eleven (2014) may have proved especially attractive to locked-down theatre-lovers because it reassures us that the show will ultimately go on. While film, TV and the Internet disappear from the post-pandemic world that Mandel depicts (along with electricity and working technology), an itinerant group called the Travelling Symphony brings Shakespeare from settlement to recovering settlement, working with nothing but human bodies and the props and costumes they gather from abandoned homes. But this article argues that what makes Mandel's novel especially apt reading amidst COVID-19 is its pervasive concern with conditions of work, or more specifically, with finding work that you really love. While presenting a virtual utopia of what Nicholas Ridout calls 'passionate amateurs', the novel provokes a reconsideration of enjoyment and fantasy in our professional and amateur attachments at a time when the conditions of work are susceptible to both transformation and new oppressions. Drawing on Eric Santner, the article suggests that Station Eleven accentuates a biopolitical irony. Perhaps what we need liberation from, most of all, is neither the discipline and numbness of a regimenting working world nor the stifling physical and social restraints of lockdown, but rather the undeadening dynamics of what Santner calls 'biopolitical animation'.